Dung beetles (Coleoptera: Scarabaeoidea) in three landscapes in Mato Grosso do Sul, Brazil - Rodrigues,MM. (2013)
Dung beetles (Coleoptera: Scarabaeoidea) in three landscapes in Mato Grosso do Sul, Brazil. Dung Beetles are important for biological control of intestinal worms and dipterans of economic importance to cattle, because they feed and breed in dung, killing parasites inside it. They are also very useful as bioindicators of species diversity in agricultural or natural environments. The aims of this paper were to study the species richness, and abundance of dung beetles, helping to answer the question: are there differences in the patterns of dung beetle diversity in three environments (pasture, agriculture and forest) in the municipality of Dourados, in the state of Mato Grosso do Sul. A total of 105 samplings were carried out weekly, from November 2005 to November 2007, using three pitfall traps in each environment. The traps were baited with fresh bovine dung, and 44,355 adult dung beetles from 54 species were captured: two from Hyborosidae and 52 from Scarabaeidae. Five species were constant, very abundant and dominant on the pasture, two in the agricultural environment, and two in the environment of Semideciduous forest. Most of the species were characterised as accessories, common and not-dominant. The species with higher abundance was Ataenius platensis Blanchard, 1844. The indexes of Shannon-Wiener diversity were: 2.90 in the pasture, 2.84 in the agricultural environment and 2.66 in the area of native forest. The medium positive presence of dung beetles in the traps in each environment were: 36.88, 42.73 and 20.18 individuals per trap, in the pasture, agricultural environment and in the native forest, respectively. The pasture environment presented a higher diversity index. The species diversity of dung beetles was superior where there was higher abundance and regularity of resource (bovine dung).